Refugee exchanges between Cameroon and Equatorial Guinea, and their socio-economic relevance, from the First World War to immediate post-independence. Issue 3 (2nd September 2021) - Njung, George N.
ABSTRACT: The paper explores the history of refugee experiences between Cameroon and Equatorial Guinea, one that transcends different historical periods. It pays particular attention to the European-engineered First World War in Africa, which triggered an unprecedented refugee situation. Digging into the deeper histories of the African refugee experiences through this case study, and particularly from the time of the war, allows for a better appreciation of the experiences as continuous global historical processes that are not peculiar to specific regions of the world. Furthermore, the paper discusses the socio-economic relevance of the refugees to their host communities, especially in circumstances where they shared ethnic affinities and cultural similarities.